Hybrid Bulk‐Heterojunction of Colloidal Quantum Dots and Mixed‐Halide Perovskite Nanocrystals for High‐Performance Self‐Powered Broadband Photodetectors. (4th May 2022) - Sulaman, Muhammad; Yang, Shengyi; Bukhtiar, Arfan; Tang, Peiyun; Zhang, Zhenheng; Song, Yong; Imran, Ali; Jiang, Yurong; Cui, Yanyan; Tang, Libin; Zou, Bingsuo
Abstract: Self‐powered broadband photodetectors exhibit excellent self‐powered and wide‐band photoresponse from visible to infrared region and attract enormous attention due to their promising applications in imaging, sensing, and optical communication. PbSe colloidal quantum dots (CQDs) and halide perovskites nanocrystals (NCs) are commonly used for photodetectors due to their strong absorption capability, tunable bandgap, and high aspect ratio. However, due to suffering from low charge carrier mobility and high trap density, the performance of individual PbSe CQDs and perovskites‐based photodetectors is not satisfactory. Integration of PbSe CQDs with inorganic mixed‐halide perovskite nanomaterials can provide an opportunity to overcome these drawbacks. In this work, a hybrid nanocomposite of PbSe CQDs blended with all‐inorganic mixed halide perovskite NCs is integrated to fabricate bulk‐heterojunction‐based high‐performance photodetectors. The transportation of photogenerated carriers is enhanced by employing electrons‐ and holes‐extracting layers. As a result, the photoresponsivity of 6.16 A W −1 and a specific detectivity of 5.96 × 10 13 Jones with an ON/OFF current ratio of 10 5 is obtained for bulk‐heterojunction photodetector ITO/ZnO/PbSe:CsPbBr1.5 I1.5 /P3HT/Au in the self‐powered mode. Meanwhile, the device performance of the fabricated photodetector is numerically simulated by using Technology Computer‐Aided Design software, and the physical mechanisms for photogenerated carriers' transportation are discussed in detail. Abstract : A hybrid nanocomposite of PbSe colloidal quantum dots blended with CsPbBr1.5 I1.5 nanocrystals is integrated for photodetectors ITO/ZnO/PbSe:CsPbBr1.5 I1.5 /P3HT/Au. As a result, a photoresponsivity of 6.16 A W −1 with a specific detectivity of 5.96 × 10 13 Jones and an ON/OFF current ratio of 10 5 is obtained in self‐powered mode. Also, the device performance is simulated with Technology Computer‐Aided Design software, and the physical mechanisms are discussed in detail.